Left Ventricular Hemodynamic Changes and Clinical Outcomes after Transcatheter Atrial Septal Defect Closure in Adults. (24th July 2014) - Ermis, Peter; Franklin, Wayne; Mulukutla, Venkatachalam; Parekh, Dhaval; Ing, Frank
Abstract Objectives The objectives of this study are to assess current management algorithms for left ventricular (LV) hemodynamic and diastolic changes following atrial septal device occlusion in adult patients. Background Percutaneous closure is now routine for atrial septal defects (ASDs). Previous studies show ventricular size normalization following percutaneous closure. Case reports have discussed the incidence of early LV dysfunction following ASD device placement with some recommending delay of closure or placement of a fenestrated device in patients with elevated LV pressures. Method All adult patients with an isolated secundum ASD who underwent percutaneous repair were included in this study. In addition to placement of the Amplatzer septal occluder, all patients had a pre and postprocedure transthoracic echocardiography performed measuring myocardial performance index (MPI). Left ventricular end diastolic pressure (LVEDP) was measured before and after balloon occlusion. Results Nineteen patients (17 female and two male) were included in this study. Average age was 47.2 years (± 12.7 years). All defects were of clinical significance with average Qp : Qs = 2.0 (± 0.6). Balloon occlusion led to a significant (P < .01) increase in LVEDP (pre‐LVEDP mean = 7.1 mm Hg, post‐LVEDP mean = 15.3 mm Hg). There was no significant change in MPI. ASD device size displayed a modest correlation relative to the change in LVEDP (R = 0.42, P = .09). Conclusions Percutaneous ASD closure induces an increase in LVEDP. Despite this, all patients tolerated device closure without complication. It appears safe to close ASDs in these patients.